Influence of natural tail streamer asymmetry and tail length on annual apparent survival of adult Magnificent Frigatebird (Fregata magnificens) - Mónica González-Jaramillo; José Luis Rangel-Salazar; Horacio de la Cueva (Revista Mexicana de Biodiversidad)
Flight traits mediated by symmetry should be constrained by mechanical or aerodynamic effects. Natural asymmetry and external tail feather length could have unfavorable effects on aerodynamic performance and affect the survival of highly aerial birds. The Magnificent Frigatebird, Fregata magnificens, is a long-lived, highly aerial seabird with a deeply forked tail, and an extraordinary division of labor between sexes. Its flight pattern is soaring and dynamic, it also has fast active flight and acrobatic maneuvers. We explore the possible effect of tail streamer asymmetry and tail length on annual apparent survival of Magnificent Frigatebirds by using 6 years (2000-2005) of capture-mark-resighting of live-encounter data analysis. Male frigatebirds showed significant differences between left and right tail streamer length, and tail asymmetry differences between sexes. Models did not find a clear effect of tail streamer asymmetry and tail length, as individual covariates, on annual apparent survival by sex. Natural variation in a secondary sexual trait like those explored here likely does not affect apparent survival. Life-history strategies such as flight pattern, breeding behavior, and tail moult may constrain any negative effects. Longer mark-resighting studies and additional modelling could answer conclusively the association between survival and flight traits in Magnificent Frigatebirds.